2014
DOI: 10.1186/1471-2458-14-808
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress in the workforce: a multilevel and longitudinal analysis of the case of regulated occupations in Canada

Abstract: BackgroundThis study uses a multidimensional theoretical model to evaluate the role of regulated occupations and working conditions in explaining psychological distress.MethodsVarious multilevel regression analyses were conducted on longitudinal data for which measures repeated over time (n1 = 36,166) were nested in individuals (n2 = 7007).ResultsResults showed that when we controlled for working conditions, family situation, the social network outside the workplace, and personal characteristics, the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 56 publications
1
15
1
1
Order By: Relevance
“…In addition, several studies performed in other occupational settings confirmed relations between working conditions and mental health problems. 63 64 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies performed in other occupational settings confirmed relations between working conditions and mental health problems. 63 64 …”
Section: Discussionmentioning
confidence: 99%
“…34 35 36 Urban living, employment, education, and being married were associated with higher level of MWB. 36 Occupation 35 and income 34 were associated with PD. Job insecurity was positively associated with PD, and lower income groups had 7.14% of higher PD than that of the normal population.…”
Section: Discussionmentioning
confidence: 96%
“…More specifically, its main goals were twofold. First, it aimed to gain an understanding of the mechanisms through which technostress leads to psychological distress (physical, psychological and behavioral symptoms [37]). Second, it aimed to evaluate the extent to which the participants attributed their stress to the technostressors identified by Ayyagari et al [23], while noting their symptoms of psychological distress, albeit without a clinical diagnosis.…”
Section: Conceptual Gap and Aims Of This Studymentioning
confidence: 99%